The Effect Of Training And Development On Employee Retention At The District DPRD Secretariat Mandailing Christmas - Afrizal; Mesra B (Yayasan Multidimensi Kreatif, 2024)
This study aimed to analyze the effect of Training and Development on Employee Retention at the Secretariat of the Regional People's Representative Council (DPRD) of Mandailing Natal Regency. The research employed a quantitative associative causal approach with a saturated sampling technique, where the entire employee population was included. Data were obtained through questionnaires distributed to all employees at the Secretariat of the DPRD of Mandailing Natal Regency.The results of the regression test showed that Training and Development had a positive and significant effect on Employee Retention. The regression coefficient of 1.539 indicated that every increase of 1 point in Training and Development led to an increase of 1.539 points in Employee Retention, assuming other variables remained constant. The t-test results showed that the null hypothesis (Ho), which stated that there was no effect of Training and Development on Employee Retention, was rejected, and the alternative hypothesis (Ha), which stated that there was a positive effect, was accepted. This was supported by the t-value of 13.408, which was greater than the t-table value of 1.66298, and the significance value of 0.000, which was less than 0.05. Furthermore, the coefficient of determination test yielded an Adjusted R Square value of 0.675 or 67.50%, indicating that Training and Development had a very high influence on Employee Retention, with 22.50% of the variability influenced by other factors not examined in this study. The high Adjusted R Square value suggested that the regression model used was adequate in explaining the variability in Employee Retention influenced by Training and Development. Overall, the findings of this study showed that improvements in Training and Development could contribute to increased Employee Retention at the Secretariat of the DPRD of Mandailing Natal Regency.